PARADIGMA FIQIH SOSIAL KH. M. A. SAHAL MAHFUDH DALAM MENJAWAB PROBLEMATIKA AKTUAL UMAT DI INDONESIA - Moh Dahlan (Universitas Islam Negeri Fatmawati Sukarno, 2016)
One of the religious movements in Indonesia who care about the fate of the backwardness of the people in its various aspects and maintenance the tradition versus modernist is NU. Therefore, the presences of NU in addition to preserve the understand of Islam of Ahlu Sunnah wal Jamaah, but also to stem the flow of radical religious movements. Therefore, KH MA Sahal Mahfudh as one of the key figures of NU then initiated a paradigm of social jurisprudence to address the problem. Based on this paradigm, the goal of this study was to explore the social paradigm of ijtihad jurisprudence by MA KH Sahal Mahfudh along with social jurisprudence product in addressing the actual problems of the people. The theoretical framework used is thought of M Amin Abdullah, while the method of this study is descriptive-analytic study. The results show that the paradigm of ijtihad jurisprudence social proposed by KH MA Sahal Mahfudh is built on reason and revelation or naqliyah and aqliyah proportionally, so using the framework of M Amin Abdullah, the paradigm of ijtihad jurisprudence proposed by KH MA Sahal Mahfudh include into interconnected entities approach category which where there is a balance between the use of aqliyah and naqliyah propositionally. The products of the legal jurisprudence was seen in building social dynamics and the livelihood of the people, both in the field ukhuwah, economics, Siyasah ‘Aliyah Samiyah, as well as the understanding of Aswaja in order to answer the problems of actual people in Indonesia